МОНГОЛ ӨРХ /ГЭР/ БҮЛИЙН TYYX СУДЛАЛЫН АСУУДАЛД - Т. Намжил (Acta Mongolica, 2013)
The issue of Mongolian family has been written incidentally in works and studies of Mongolian researchers and studiers. The reason to write this book is lack of works and studies about historj of Mongolian family in Mongolia. The origin of family and its change as well as relative structure and its feature of the period of nomadic Mongolian clan structure /both ofmatriarchal and patriarchal systems/ are written in this book trom family, historical and ethnic poinl of view based on the archeological findings. I have tried to determine the similarities between nomadic Mongolian and EastenVWesterns families^ tradition and customs in the book. The book includes the defining dictionary of words related to the study of history of Mongolian family. The book is tor researches and studiers /students, masters and doctorates/ who study and interested in nomadic Mongolian culture and civilization.